Early changes in tests of peripheral nerve function during oxaliplatin treatment and their correlation with chemotherapy‐induced polyneuropathy symptoms and signs. (2nd August 2019) - Krøigård, T.; Svendsen, T. K.; Wirenfeldt, M.; Schrøder, H. D.; Qvortrup, C.; Pfeiffer, P.; Gaist, D.; Sindrup, S. H.
Abstract : Background and purpose: Assessment of the severity of chronic peripheral neuropathy during oxaliplatin treatment is based on symptoms. Efforts to adjust the total dose of oxaliplatin to prevent severe neuropathy can be complicated by the worsening of neuropathy symptoms following treatment. Objective measures of the structure and function of peripheral nerves during early phases of treatment may aid in determining the optimal oxaliplatin dose in individual patients. Intraepidermal nerve fibre density (IENFD) has been suggested as an early marker of peripheral neuropathy. Methods: Sixty patients were examined before treatment and following 25% and 50% of the total planned oxaliplatin dose. Fifty‐five of them were also examined at completion of chemotherapy and 6 months later. IENFD in skin biopsies from the distal leg, nerve conduction studies and quantitative sensory testing at the dorsum of the foot were performed. Forty‐six healthy subjects were examined at baseline and after 6 and 52 weeks for comparison. Results: Intraepidermal nerve fibre density was not reduced during treatment. Sural nerve amplitude and conduction velocity, vibration detection thresholds, mechanical detection threshold and cold detection threshold were significantly reduced during treatment. Compared to reference values and spontaneous changes in healthy subjects, the largest proportions of patients with deterioration were found for vibration detection thresholds followed by nerve conduction studies, mechanical detection threshold, cold detection threshold and IENFD. Conclusions: Significant changes were most pronounced for measures of large nerve fibre function, especially vibration sensation. Skin biopsies do not seem to provide a clinically relevant objective measure of peripheral nerve deterioration during oxaliplatin treatment.